2007
DOI: 10.4028/www.scientific.net/kem.330-332.299
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Silver-Hydroxyapatite/Titania Nanoparticles on Oral Bacteria

Abstract: Since bacterial accumulation surrounding biomaterials has pathogens known to cause the biomaterials centered infection, it may be important to develop some kind of biomaterial with antibacterial activity as well as biocompatibility. This study focused on evaluating the antibacterial activity of silver-hydroxyapatite/ Titania nanoparticles (Ag-nHA/nTiO2) against oral bacteria with agar dilution method. Bacteria were seeded on agar plate containing antibacterial material with different concentrations after incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Further, the negatively charged Gram positive bacterial cell wall bind with more Ag ions which results in less number of AgNPs interacting with the plasma membrane thereby protecting the plasma membrane from the reactive oxygen species generated by the AgNPs leading to increased resistance observed. [43]. Further silver NPs mediate binding with DNA, protein denaturation, and respiratory functions leading to cell death [1,9,38].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Further, the negatively charged Gram positive bacterial cell wall bind with more Ag ions which results in less number of AgNPs interacting with the plasma membrane thereby protecting the plasma membrane from the reactive oxygen species generated by the AgNPs leading to increased resistance observed. [43]. Further silver NPs mediate binding with DNA, protein denaturation, and respiratory functions leading to cell death [1,9,38].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…14,15 A previous study has proved that the Ag + provided inhibitive effects on oral bacteria, such as Porphyromonas gingivalis, Prevotella intermedia, and Fusobacterium nucleatum. 16,17 Therefore, the incorporation of silver ions or silver compounds in sealers may be advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…The attachment of AgNPs to the surface of microbial cells was observed in this study using SEM and has also been reported by several groups. 17,19 Oza et al 20 reported that the antibacterial effect of AgNPs may be due to penetration of released Ag ions in bcterial cell wall. AgNPs can disrupt the cell wall and rapidly detach the biofilms.…”
Section: Discussionmentioning
confidence: 99%